IMPLEMENTASI PENDIDIKAN KARAKTER RELIGIUS OLEH GURU DALAM PEMBELAJARAN SOSIOLOGI DI SMA YPK PONTIANAK - Megawati, Megawati; Sulistyarini, Sulistyarini; Ulfah, Maria (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study would to determined the implementation of religious value in character education by teacher in sociology learning in SMA YPK Pontianak and to find out the factors that influence the implementation of character education in religious values in sociology learning in SMA YPK Pontianak. The method used in this study was descriptive method with qualitative approach. The data sources of the study were the students of grade X IIS and the sociology teacher of grade X IIS, interview and observation’s result. The results of this study show that the implementation of religious value in character education in sociology learning involve greeting, pray before the lesson begins, the teacher implements character education in the learning process, appreciating religious diversity, the teacher also teaches about the religious dimensions, such relationship between individuals and individuals, individuals and God, individuals and the environment, religious worship, prayer after the lesson ends. Factors that influence the implementation of the character education of religious values in SMA YPK Pontianak were the religious diversity and the inadequate facilities of house worship.Keywords: Implementation, Religious Character Education, SMA.